Behavior of Flexible Buried Pipes Under Geocell Reinforced Subbase Subjected to Repeated Loading - Fattah, Mohammed Yousif; Hassan, Waqed Hammed; Rasheed, Sajjad Emad (International journal of geotechnical earthquake engineering, 2018)
The present article constitutes an experimental investigation of the behavior of buried PVC pipes. A number of laboratory experiments were conducted using PVC pipes which were buried in a medium sand layer, below a subbase layer, reinforced with geocells. They were subject to repeated dynamic load amplitudes of 0.5 and 1 ton and loading frequencies of 0.5, 1 and 2 Hz, to study the effects of the geocell reinforcement layer, in terms of the amount of stress reaching the pipe crown and the vibration of the pipe. A 3D numerical model was also developed to investigate the performance of the geocell above the buried pipe. The predicted characteristics of the buried pipes were validated using the experimental data. The results showed that geocell reinforcement decreases both crown vibration by 35%, and the vertical pressure reaching the pipe by 41%. The numerical models have a good fit with the experimental work results, both confirming that geocell reinforcement has a significant role to play regarding increasing the safety of pipes.